2020
DOI: 10.1016/j.jamda.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 In-Hospital Mortality and Use of Renin-Angiotensin System Blockers in Geriatrics Patients

Abstract: Objective The role of treatment with renin-angiotensin-aldosterone system blockers at the onset of COVID-19 infection is not known in geriatric population. The aim of this study was to assess the relationship between angiotensin receptor blockers (ARB) and an ACE inhibitor (ACEI) use and in-hospital mortality in geriatric patients hospitalized for COVID-19. Design This observational retrospective study was conducted in a French geriatric department. Patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
5
25
1
Order By: Relevance
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the selected studies are summarized in Table 3 , which indicates that the included studies came from 7 different countries. Six of the studies were conducted in Italy 19 , 20 , 21 , 22 , 4 were conducted in Spain 27 , 28 , 32 , 33 , and 1 study per country was conducted in Belgium 23 , France 24 , South Korea 25 , Turkey 26 , and Japan 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent additional studies also report that treatment with ARBs and ACE-Inhs. is associated with reduced disease severity and decreased mortality rates in COVID-19 patients ( Adrish et al, 2020 ; C. Chen et al, 2020 ; R. Chen et al ; H. K. Choi et al, 2020 ; Genet et al, 2020 ; Matsuzawa et al, 2020 ; Megaly & Glogoza, 2020 ; X. Meng et al, 2020 ; Negreira-Caamaño et al, 2020 ; Palazzuoli et al, 2020 ; Yahyavi et al, 2020 ; Y. Yuan et al, 2020 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…Moreover, Supplementary Table S1 summarizes the reported underlying comorbidities and the P values reported by each study to determine any significant differences between the 2 groups of COVID‐19 patients who did or did not use ACEi/ARBs. Only 2 studies reported significantly higher proportions of the control patients with underlying chronic kidney disease ( P = .001) 27 or dementia ( P = .003) 41 . However, both these studies as well as 15 other studies reported that the ACEi/ARBs groups had significantly higher proportions of patients with different comorbidities.…”
Section: Resultsmentioning
confidence: 89%